A Review on the Role of Phytoconstituents Chrysin on the Protective Effect on Liver and Kidney - Sarmah, Debika; Sengupta, Rupa (Current Drug Discovery Technologies, 2024)
Background: The chance of contracting significant diseases increases due to an unhealthy and contemporary lifestyle. Chrysin is a flavonoid of the flavone class in numerous plants, including Passiflora and Pelargonium. Chrysin has long been used to treat a variety of illnesses. Chrysin, an essential flavonoid, has many pharmacological actions, including anticancer, antiviral, anti-inflammatory, anti-arthritic, depressive, hypolipidemic, hepatoprotective, and nephroprotective activity. Purpose: This explorative review was commenced to provide a holistic review of flavonoids confirming that Chrysin has a therapeutic potential on the liver and kidney and reduces the hepatotoxicity and nephrotoxicity induced by diverse toxicants, which can be helpful for the toxicologists, pharmacologists, and chemists to develop new safer pharmaceutical products with chrysin and other toxicants. Study Design: The most relevant studies that were well-explained and fit the chosen topic best were picked. The achieved information was analyzed to determine the outcome by screening sources by title, abstract, and whole work. Between themselves, the writers decided on the studies to be considered. The necessary details were systematically organized into titles and subtitles and compressively discussed. Method: The information presented in this review is obtained using targeted searches on several online platforms, including Google Scholar, Scifinder, PubMed, Science Direct, ACS publications, and Wiley Online Library. The works were chosen based on the inclusion criteria agreed upon by all authors. Results: Chrysin is a promising bioactive flavonoid with significant health benefits, and its synthetic replacements are being utilized as pharmaceuticals to treat various diseases. Findings revealed that Chrysin exhibits hepatoprotective actions against several hepatotoxicants like 2,3,7,8 tetrachlorodibenzo- p-dioxin, carbon tetrachloride (CCl4), cisplatin, and others by lowering the levels of liver toxicity biomarkers and enhancing antioxidant levels. Additionally, chrysin has potential nephroprotective properties against various nephrotoxicants, like Cisplatin, Doxorubicin, Paracetamol, Gentamicin, Streptazosin, and others by dropping kidney toxicity marker levels, reducing oxidative stress, and improving the antioxidant level. Conclusion: According to this revised study, chrysin is a promising phytoconstituent that can be utilized as an alternate treatment for various medications that cause hepatotoxicity and nephrotoxicity. With active chrysin, several dosage forms targeting the liver and kidneys can be formulated.
Keywords: nephroprotective